Smartphone: Bagaimana Pengaruh terhadap Motivasi Belajar Siswa Sekolah Dasar? - Sani, Khairul; Adiansha, Adi Apriadi (Jurnal Ilmiah Mandala Education (JIME), 2021)
The use of smartphones can be detrimental to improving the quality of students, especially in elementary schools, this is influenced by excessive smartphone use. The purpose of this study was to explain the effect of smartphones on student motivation in elementary schools in Bolo District. This research was conducted at the Bolo District Elementary School. The sample used was 84 students. This research is a quantitative approach using a survey method. This research has stages: observation of the research location, preparation of questionnaires, distribution of questionnaires, validity testing, data collection, processing of research results, analysis of research results, and discussion. The results showed that the effect of smartphones on student motivation in elementary school even though it is in a low category. Suggestions as recommendations: students do not use smartphones excessively both at school and at home. Parents and teachers always supervise children, especially using smartphones every day because the effect of smartphones on student learning motivation is very low